Efek Lumatan Daun Dewa (Gynura Segetum) dalam Memperpendek Waktu Penyembuhan Luka Bersih pada Tikus Putih - Setyoadi; Sartika, Dina Dewi (Jurusan Keperawatan FIKES UNSOED, 2010)
Gynura segetum leaves have been identified to have some pharmacologic effects. Gynura segetum have chemical material such as saponin, flavonoid, and atsiri oil, because of this Gynura segetum suppose to be anti inflammation and healing time. This research conducted to identify the effect of pulverized Gynura segetum leaves on shortening time of healing clean wound. It was a true experimental methode with sample consist of 18 mice with steril incision wound, which by simple random sampling method which then devided into three groups : group I (given pulverized Gynura segetum leaves), group II (given pulverized Gynura segetum leaves twice a day), and group III (control group given NaCl 0.9%). Parameter being measured was the healing time of clean wound. The results of one-way ANOVA test was in a significant difference in healing time between group I,II, and III by value 0.000 (p≤:0.05). The post hoc test results was in a significant difference in group I and II by p value 0.005 (p≤0.05), group I and III by p value 0.000 (p≤:0.05), group II and III by p value 0.000 (p≤:0.05). Conclusion : 1) pulverized Gynura segetum leaves shortens the healing time of clean wound compared to control group, 2) pulverized Gynura segetum leaves given twice a day is more effective in shortening healing time of clean wound. However, it was necessary to conduct similar research with variant frequencies or different parameters to identify the effects of pulverized Gynura segetum leaves in shortening the healing time of clean wound.